Mesenchymal Stem Cells in Sepsis and Associated Organ Dysfunction: A Promising Future or Blind Alley? - Jan Horák; Lukáš Nalos; Vendula Martínková; Jan Beneš; Milan Štengl; Martin Matějovič (Stem Cells International)
Sepsis, newly defined as a life-threatening organ dysfunction caused by a dysregulated host response to infection, is the most common cause of death in ICUs and one of the principal causes of death worldwide. Although substantial progress has been made in the understanding of fundamental mechanisms of sepsis, translation of these advances into clinically effective therapies has been disappointing. Given the extreme complexity of sepsis pathogenesis, the paradigm “one disease, one drug” is obviously flawed and combinations of multiple targets that involve early immunomodulation and cellular protection are needed. In this context, the immune-reprogramming properties of cell-based therapy using mesenchymal stem cells (MSC) represent an emerging therapeutic strategy in sepsis and associated organ dysfunction. This article provides an update of the current knowledge regarding MSC in preclinical models of sepsis and sepsis-induced acute kidney injury. Recommendations for further translational research in this field are discussed.